Performance monitoring: A study on ISO 14001 certified power plant in Malaysia - Jor, Jee Wong; Mohammad Omar, Abdullah; Rubiyah, Baini; Yie, Hua Tan (Elsevier Ltd., 2017)
ISO 14001 has been widely applied by various power plant sectors to manage their plants’ performance. This paper aims to conduct monitoring on the environmental and operational performances of an ISO 14001 certified coal power plant in Malaysia. This work suggests some area for improvements for those performance parameters which show inconsistency and downtrend, statistically. Relevant environmental and operational performance parameters were selected as the indicators for air quality, generating efficiency, power availability and reliability. The environmental parameters are the air quality parameters which include Total Suspended Particulate, Particulate Matter up to 10 μm in size and Sulfur Oxides. Thermal Efficiency and Equivalent Availability Factor were selected as parameters for generating efficiency and availability. For reliability, the parameters are Equivalent Unplanned Outage Factor and Equivalent Planned Outage Factor. Overall findings showed that better performance was recorded on environmental aspect, suggesting more focuses were put on regulatory concerns to ensure high environmental compliances. The present work provides some of the approaches in achieving more effective ISO 14001 implementation in power plant industry, in tandem with the policy of Malaysia government towards a more self-regulating manner. It demonstrates some relevant evidences toward treating operational improvement as equally significant and beneficial efforts for economic gain and environmental enhancement. Furthermore, this study provides a useful structure method for future research on performance monitoring as well as for the reference of other certified and non-certified ISO 14001 power plants.